Tiny Tumor with a Bigger Challenge: A Journey Through Uncertainty Using Neuro-Endoscopy in a Case of Recurrent Cushing Disease (Bangladesh Journal of Neurosurgery, 2026)
Cushing disease caused by ACTH-secreting pituitary microadenomas remains a surgical  challenge, especially in recurrent cases with distorted anatomy. We report a case of a  35-year-old male with recurrent Cushing disease following unsuccessful initial transsphenoidal  surgery. Re-operated using endoscopic endonasal transsphenoidal approach, this  case illustrates the complexity of navigating scarred anatomical landmarks and ensuring  complete tumor excision. The patient demonstrated marked clinical and biochemical  improvement postoperatively, emphasizing the importance of meticulous surgical  technique in reoperative endoscopic pituitary surgery(Cappabianca et al., 2014; Losa et  al., 2000).  Bang. J Neurosurgery 2025; 14(2): 138-141